Influence factors analysis of removing heavy metals from multiple metal-contaminated soils with different extractants - Xia, Wen-bin; Li, Xin; Gao, Hui; Huang, Bao-rong; Zhang, Hui-zhi; Liu, Yun-guo; Zeng, Guang-ming; Fan, Ting (Journal of Central South University of Technology. Science & technology of mining and metallurgy, 2009)
Some key factors on the heavy metals removal efficiencies were studied when soil washing technology was used in the remediation of soils contaminated by multiple heavy metals. The results show that the dissolubilities of Cu and Zn are promoted by humic acids, but Pb and Cd are inhibited by humic acids; heavy metals in the clay are more difficult to be extracted than silt; the strong acidic soils can cause the protonation of EDTA and weaken its extracting ability; EDTA is effective for extracting Pb and Cd, while oxalate (OX) is effective for extracting Cu and Zn; and biosurfactant can be used as additive to improve the removal of some particular heavy metals.